The Average Lifespan of Patients Discharged from Hospital with Heart Failure - Alter, David A. (Springer-Verlag, 2012)
BACKGROUND: There are no life-tables quantifying the average life-spans of post-hospitalized heart failure populations across various strata of risk. OBJECTIVE: To quantify the life-expectancies (i.e., average life-spans) of heart failure patients at the time of hospital discharge according to age, gender, predictive 30-day mortality heart failure risk index, and comorbidity burden. DESIGN: Population-based retrospective cohort study. SETTING: Ontario, Canada. PATIENTS: 7,865 heart failure patients discharged from Ontario hospitals between 1999 and 2000. MEASUREMENTS: Data were obtained from the Enhanced Feedback for Effective Cardiac Treatment EFFECT provincial quality improvement initiative. All patients were linked to administrative data, and tracked longitudinally until March 31, 2010. Detailed clinical variables were obtained from medical chart abstraction, and death data were obtained from vital statistics. Average life-spans were calculated using Cox Proportion Hazards models in conjunction with the Declining Exponential Approximation of Life Expectancy (D.E.A.L.E) method to extrapolate life-expectancy, adjusting for age, gender, predicted 30-day mortality, left ventricular function and comorbidity, and was reported according to key prognostic risk-strata. RESULTS: The average life-span of the cohort was 5.5 years (STD +/− 10.0) ranging from 19.5 years for low-risk women of less than 50 years old to 2.9 years for high-risk octogenarian males. Average life-spans were lower by 0.13 years among patients with impaired as compared with preserved left ventricular function, and by approximately one year among patients with three or more as compared with no concomitant comorbidities. In total, 17.4 % and 27 % of patients had died within 6 months and 1 year respectively, despite having predicted life-spans exceeding one-year. LIMITATIONS: Data regarding changes in patient clinical status over time were unavailable. CONCLUSIONS: The development of risk-adjusted life-tables for heart failure populations is feasible and mirrored those with advanced malignant diseases. Average life span varied widely across clinical risk strata, and may be less accurate among those at or near their end of life.